Fishing for the Brazilian sardine, Sadinella brasiliensis (Steindachner) (Osteichthyes: Clupeidae) and its by-catch off Rio de Janeiro State (Brazil) - Paiva, Melquíades Pinto; da Mota, Paulo César Silva (Arquivos de Ciências do Mar, 2018)
This paper deals with the fishing for the Brazilian sardine, Sardinella brasiliensis (Steindachner), and its by-catch along the coast of Rio de Janeiro State (Brazil), based on log-book records in period 1993-1997. The mean abundance indices of the sardine and its by-catch were 6.1 t per haul and 2.2 t per haul, yielding a 1.0:0,4 catch rate. The annual cycle of sardine catches comprises periods of higher production and abundance in April-June (autumn) and lower production and abundance in July-Setember (winter). There was found to be a certain degree of coincidence in the cycles of production and abundance for the sardine and its by-catch. The main associated species found in the schools are Brazilian menhaden, Brevoortia aurea (Spix), bigmouth-anchovy, Cetengraulis edentulus (Cuvier), and Atlantic thread-herring, Opisthonema oglinum (Le Sueur). The most important predators are chub-mackerel, Scomber japonicus (Houttuyn), blue-runner, Carangoides crysos (Mittchill), and Atlantic little-tuna, Euthynnus alletteratus (Rafinesque). The skipjack tuna, Katsuwonus pelamis (Linnaeus), is an important predator of Brazilian sardine, but it does not get caught by the purse-seines.